Exploring the relationship between exposure to COVID-19 and donations during the COVID-19 pandemic: The mediating roles of emotions and risk perception - Bao, Yun; Zhang, Yan; Wang, Junxiu (Frontiers in Psychology, 2023)
Objective: Public emergency events like the COVID-19 pandemic are special occasions that need immediate massive funding from public donations. Thus, understanding the determinants of donation behaviors under public emergencies is important for both researchers and practitioners. This study investigated the effect of personal and local exposure to incidences of COVID-19 on donation behaviors. Specifically, we examined the mediating effects of risk perception and emotions on the relationship between exposure to COVID-19 and donation behaviors. Methods: The data were from a survey distributed in China between March 20th and 30th, 2020. Participants’ donation choice at the end of the survey was used to measure their donation behaviors. Participants’ emotions, risk perception, and personal exposure were assessed in the questionnaire. Local exposure was the thirty-day confirmed cases obtained from the National Health Commission of the People's Republic of China. A total of 8720 participants (Mean age = 28.91, 43.6% females) completed the online survey. Results: Based on the results from the mediation analysis, we found that people with stronger positive and negative emotions, higher risk perception, and more personal exposure to COVID-19 were more likely to donate. Furthermore, the effects of both personal and local exposure on donations are mediated by risk perception and negative emotion. Both higher personal and local exposure led to stronger negative emotions and higher risk perception, which in turn led to more donation behaviors. Discussion: This study extends our knowledge of donation behaviors during public emergencies. Our results suggest that policymakers and charity organizations should elicit stronger emotions and risk perception by exposing the severity of the disaster in advertisements to promote donations.